2002
DOI: 10.1007/s004420100796
|View full text |Cite
|
Sign up to set email alerts
|

Plant-insect communities and predator-prey ratios in field margin strips, adjacent crop fields, and fallows

Abstract: The management of field margin strips for the enhancement of biodiversity of plant-insect communities and natural-enemy populations was studied on experimental farms near Göttingen (Germany). Young and old, sown and naturally developed field margin strips were compared and differences to large fallows established. The five types of field margin strips (around cereal fields) were: (1, 2) 1- or 6-year-old naturally developed strips, (3) strips sown with a Phacelia mixture, (4) strips sown with a mixture of 19 wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
114
0
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(122 citation statements)
references
References 41 publications
2
114
0
6
Order By: Relevance
“…Predators form an important aspect of our study, as some of these invertebrates are beneficial to farmers because of their potential as pest control (Carter and Rypstra 1995;Obrycki and Kring 1998;Collins et al 2002). Predator abundance decreased with progressing age of the margins (in contrast to Denys and Tscharntke 2002, but in line with Woodcock et al 2008), due probably to the vegetation developing from a recently sown, open situation to higher standing biomass and a denser sward, although in our analyses this development was only expressed by a significant effect of age (Noordijk et al 2010). Ground-dwelling predatory invertebrates often depend on open, sun-lit places where they can easily move to find prey (Harvey et al 2008).…”
Section: Invertebrate Richness and Abundancesmentioning
confidence: 63%
See 2 more Smart Citations
“…Predators form an important aspect of our study, as some of these invertebrates are beneficial to farmers because of their potential as pest control (Carter and Rypstra 1995;Obrycki and Kring 1998;Collins et al 2002). Predator abundance decreased with progressing age of the margins (in contrast to Denys and Tscharntke 2002, but in line with Woodcock et al 2008), due probably to the vegetation developing from a recently sown, open situation to higher standing biomass and a denser sward, although in our analyses this development was only expressed by a significant effect of age (Noordijk et al 2010). Ground-dwelling predatory invertebrates often depend on open, sun-lit places where they can easily move to find prey (Harvey et al 2008).…”
Section: Invertebrate Richness and Abundancesmentioning
confidence: 63%
“…However, only a limited number of papers have been published on the development of invertebrate communities in field margins after initial establishment (more papers have been published on plant succession, e.g., Kleijn et al 1998;Critchley et al 2006;Manhoudt et al 2007;Musters et al 2009). Most of them found in increase with age of the margins (Denys and Tscharntke 2002;Olson and Wäckers 2007;Frank and Reichhart 2004;Woodcock et al 2008;Musters et al 2009), although Woodcock et al (2008) found predatory beetles to peak in the second year after establishment and to decrease in 2 year thereafter. However, none of these studies deal with a broad range of invertebrate groups and only Musters et al (2009) and Denys and Tscharntke (2002) discuss patterns over a considerable period of time.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…The more mobile taxa had, on average, less similar communities on the field and farm level than plants (Table 4), i.e., a field and b field represented a greater proportion of c diversity for carabids, and a farm , b farm , and b region represented a greater proportion of c diversity for birds in comparison to plants. One possible explanation are spillover effects from the adjacent non-crop habitats for more mobile taxa, which could lead to variance in the local species composition (Hendrickx et al 2009), as supported by several studies stressing the importance of the surrounding landscape and field margins for the within field carabid community (Denys and Tscharntke 2002, Purtauf et al 2005, Schweiger et al 2005, Hendrickx et al 2007, Bata´ry et al 2008, Smith et al 2008. Likewise, the importance of species-rich field margins and seminatural habitats for within-field species richness has already been shown for many other arthropod taxa depending on body size (ability for mobility; , Schweiger et al 2005, Holland et al 2009) and farmland birds (Vickery et al 2002.…”
Section: Differences In Spatial Diversity Patterns Between Plants Camentioning
confidence: 99%
“…Field margins are extensively managed strips of land, often sown with forbs and grasses, that have been established in a range of countries, including the United Kingdom ), Switzerland (Zollinger et al 2013), Germany (Denys and Tscharntke 2002), France (Cordeau et al 2012) and the Netherlands (Noordijk et al 2010). Field margins generally contain higher densities of arthropods than agricultural land, and they are a highly preferred foraging habitat for Skylarks and other farmland passerines (Perkins et al 2002;Kuiper et al 2013).…”
Section: Introductionmentioning
confidence: 99%